ESTIMATION OF THE PERCENTAGE OF LACTOFERRIN AND IMMUNE PROTEINS IgG IN BUFFALO COLOSTRUM WITHIN FIVE DAYS OF BIRTH - Saja Qasim; Taha Mohammed; Sumyia Badawi (Mesopotamia Journal of Agriculture)
The study aimed to estimate the proportions of lactoferrin and IgG immunoglobulins, and to separate lactoferrin from buffalo colostrum. Buffalo colostrum samples were collected from the first hour to the five days after birth. Then, the percentages of lactoferrin were estimated using HPLC technology. The percentage of IgG using an ELISA device in colostrum, after that the lactoferrin protein was separated from the colostrum by the sodium dodecyl sulfate-polyacrylamide Gel electrophoresis (SDS-PAGE) method, and the protein was extracted from the Gel (SDS-PAGE). The results showed that the lactoferrin level was higher on the first day, after and decrease within days of milk production. The IgG level was higher in the first hour; afterward it decreased and then increased on the fourth day, reaching 30.46 mg/ml. Lactoferrin was separated by electrophoresis based on the molecular weight of the standard lactoferrin sample. Clear lactoferrin separation areas appeared on the acrylamide Gel. Lactoferrin was then extracted by SDS-PAGE and eluted from the Gel.